Ginsenoside Rh7 Suppresses Proliferation, Migration and Invasion of NSCLC Cells Through Targeting ILF3-AS1 Mediated miR-212/SMAD1 Axis - Chen, Xiangbo; Liu, Wenguang; Liu, Bao (Frontiers in Oncology, 2021)
It is reported that ginsenosides have a significant anti-tumor effect on a variety of tumors. However, the role and mechanism of Rh7 in non-small cell lung cancer (NSCLC) are unclear. In this study, we aimed to study the anti-tumor effect of Rh7 on the proliferation and progression of NSCLC. Bioinformatics analysis showed that ILF3-AS1 was regulated by ginsenoside Rh7 in NSCLC. Down-regulation of ILF3-AS1 could significantly inhibit the proliferation, metastasis and invasion of NSCLC. In addition, ILF3-AS1 negatively controlled miR-212, which in turn targeted SMAD1 expression, thereby regulating NSCLC cell viability and apoptosis. Our results indicate that ILF3-AS1 can be used as a diagnostic and therapeutic target for non-small cell lung cancer. It is discovered for the first time that ginsenoside Rh7 inhibits the expression of ILF3-AS1 and exerts antitumor effects.